THE CHALLENGES OF ENGLISH TEACHERS IN CHOOSING TEACHING METHODS FOR TEACHING DESCRIPTIVE TEXT AT SMP NEGERI 7 KISARAN - Syavira Yulistia; Rika Rika (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
This study aims to describe and investigate the challenges faced by English teachers in choosing teaching methods to teach description texts in SMP Negeri 7 Kisaran. This study uses qualitative descriptive research design. The data were taken from 2 English teachers who taught at SMP Negeri 7 on the description text material for the seventh grade with interviews and documentation. The data analysis in this study used the Miles and Huberman’s model with three stages, there are data reduction, data display and withdrawal conclusion. The study found that the challenges faced by teachers in choosing teaching methods to teach descriptive text materials are limited vocabulary, lack of student interest, limited time, limited media and goal of teaching. Teachers who taught at SMP Negeri 7 Kisaran said that the most challenge they faced in choosing teaching methods for descriptive text material was limited students of vocabulary. The solutions from the teachers when faced the challenges are using interesting media, utilizing technology, and using the Grammar Translation Method.Keywords: Challenges, Teaching Methods, Descriptive Text